Matrix Metalloproteinase 13 Expression in Response to Double‐Stranded RNA in Human Chondrocytes1. Issue 5 (23rd April 2013) - Radwan, Marta; Gavriilidis, Christos; Robinson, John H.; Davidson, Rose; Clark, Ian M.; Rowan, Andrew D.; Young, David A.
Abstract Objective To investigate the mechanism of matrix metalloproteinase 13 (MMP‐13) expression in chondrocytes via pattern‐recognition receptors (PRRs) for double‐stranded RNA (dsRNA). Methods Differential expression of PRRs was determined by real‐time reverse transcription–polymerase chain reaction (RT‐PCR) of RNA from patients with osteoarthritis (OA) and patients with femoral neck fracture (as normal control). Isolated human articular chondrocytes and the chondrosarcoma cell line SW‐1353 were activated with poly(I‐C) of different molecular weights as a dsRNA mimic, and changes in gene and protein expression were monitored by real‐time RT‐PCR and immunoblotting, respectively. Results The dsRNA signaling moieties Toll‐like receptor 3 (TLR‐3), retinoic acid–inducible gene 1 (RIG‐1), and nucleotide‐binding oligomerization domain–like receptor X1 were all differentially expressed in OA cartilage compared to normal cartilage, as determined by gene expression screening. Depletion of the dsRNA‐sensing receptors TLR‐3, RIG‐1, or melanoma differentiation–associated gene 5 (MDA‐5) suppressed the induction of MMP13 messenger RNA (mRNA) expression by poly(I‐C), regardless of its mode of delivery. In addition, depletion of the downstream transcription factor interferon regulatory factor 3 resulted in reduced induction of MMP13 mRNA expression by poly(I‐C). Conclusion Signaling by dsRNA in chondrocytes requires a range of PRRs, including TLR‐3, RIG‐1, and MDA‐5, for the full‐induction of MMP13, thus providing tight regulation of a gene critical for maintenance of cartilage integrity. Our data add to the understanding of MMP13 regulation, which is essential before such mechanisms can be exploited to alleviate the cartilage destruction associated with OA.